Acquired Factor X Deficiency in Patients With Primary Light Chain Amyloidosis - Siroj Dejhansathit MD; Attaya Suvannasankha MD (SAGE Publishing, 2019)
Acquired factor X (FX) deficiency is a rare but serious complication of primary amyloidosis, presumably caused by the binding of amyloid proteins to the clotting factors. The prolonged prothrombin time, partial thromboplastin time, and low FX level, which are correctable by mixing study, are the disease hallmarks. An immediate goal of care is to stop bleeding. Clotting factor replacement requires close monitoring of coagulogram and FX levels due to varying FX clearance among patients. High-purity FX is currently approved for hereditary FX deficiency and has been successfully used in some acquired FX deficiency cases. Ongoing bleeding risk complicates the treatment decision. Novel therapies yielding rapid and deep response reduce amyloid protein production and improve long-term outcome.